Estimates of in situ digestibility and fibrous compounds in feeds for ruminants - Kuwahara, Frank Akiyoshi [UNESP]; Souza, Gilberto Batista De; Soares, Viviane Faria; Ferreira, Reinaldo De Paula; Costa, Ciniro [UNESP]; Meirelles, Paulo Roberto De Lima [UNESP] (Editora da Universidade Estadual de Maringá - EDUEM, 2015)
Current paper assesses the relationship between in situ incubation time, particle size and types of materials on estimates of indigestible fractions of dry matter (iDM) and neutral detergent fiber (iNDF) in cattle feed and feces. Samples of soybean meal, alfalfa and feces of cattle fed on high concentrated diets were analyzed. The samples were processed in a Wiley mill, with 0.5 and 1.5 mm porosity for food and 1.5 mm for feces, which were packed in 4 × 5 cm F57 bags (Ankon(r)) and nonwoven fabric (100 g m-2) of two brands. The material was divided into two groups, with and without treatment with acetone, and five replications. Samples of each group were incubated in the rumen of a multiparous cow adapted to a 70:30 diet, forage:concentrate diet, for 240 hours. The iDM and iNDF levels were evaluated sequentially to interpret the percentages of undigested material. Data underwent analysis of variance (ANOVA, p < 0.05) and means were compared by Tukey's test (p < 0.05). Material, size of particles and incubated material affected iDM and iNDF estimates.

A premissa é avaliar a relação do tempo de incubação in situ, tamanho de partículas e tipos de materiais sobre as estimativas das frações indigestíveis da matéria seca (MSi) e da fibra em detergente neutro (FDNi) em alimentos e fezes bovinas. Estudaram-se amostras de farelo de soja, alfafa e fezes de bovinos alimentados com dietas com alto concentrado. As amostras foram processadas em moinho de facas com peneiras de porosidade 0,5 e 1,5 mm para alimentos e 1,5 para fezes, acondicionadas em sacos de F57 (Ankon(r)) e tecido não tecido (100 g m-2) de duas marcas na dimensão 4 × 5 cm. Os materiais foram divididos em dois grupos, com e sem tratamento com acetona e cinco repetições, incubadas no rúmen de uma vaca multípara adaptada à dieta 70:30, volumoso:concentrado, respectivamente, por 240h. Os teores de MSi e FDNi foram avaliados sequencialmente para interpretação das porcentagens de material não digerido, e os dados foram submetidos à análise de variância (Anova, p < 0,05), e as médias comparadas posteriormente pelo teste de Tukey (p < 0,05). Houve efeito do tipo de material utilizado, tamanho de partículas e material incubado sobre as estimativas de MSi e FDNi.
Estimativa de digestibilidade in situ e componentes fibrosos em alimentos para ruminantes
Keywords: digestion; neutral detergent fiber; nonwoven fabric; F57.; digestão; fibra em detergente neutro; tecido não tecido; F57.